2020
DOI: 10.1088/1361-6528/ab6679
|View full text |Cite
|
Sign up to set email alerts
|

Height patterning of nanostructured surfaces with a focused helium ion beam: a precise and gentle non-sputtering method

Abstract: This work presents a new technique for surface patterning with focused ion beams. The technique is based on chemical decomposition in the bulk of a polymer substrate with negligible surface sputtering effects. By using a focused helium ion beam, generated in a helium ion microscope, we show that the surface height of polymethyl methacrylate substrates can be patterned with nanometer depth precision, while preserving the essential features of the nanostructures prefabricated on this surface. The key factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…The primary reason for this choice was the difference in their microstructures, specifically in the availability of structural defects capable of providing the release of gases from radiolysis. As it has been shown before [4], the as-deposited 15 nm Pt 60 Pd 40 thin films contain arrays of nanoscale cracks. In contrast, our studies have not revealed any cracks or other discontinuities in the as-deposited Au thin films.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…The primary reason for this choice was the difference in their microstructures, specifically in the availability of structural defects capable of providing the release of gases from radiolysis. As it has been shown before [4], the as-deposited 15 nm Pt 60 Pd 40 thin films contain arrays of nanoscale cracks. In contrast, our studies have not revealed any cracks or other discontinuities in the as-deposited Au thin films.…”
Section: Introductionsupporting
confidence: 57%
“…The observed increase in the surface descending rates and in the saturation level upon irradiation with Ne + and Ga + ions ( Figure 2) indicate that, in those cases, both surface sputtering and subsurface volume shrinkage contribute to the changes in depth across the sample. According to our previous study [4], the reduction in surface height of the metal-coated PMMA surface is controlled by two major parameters. The first parameter is the irradiation fluence of He + ions, which determines the total amount of radiation energy dissipated by the ions over their entire path in the sample.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations